Because I had a teacher - Yamada, Kobi.; Russell, Natalie (Seattle, WA : Compendium, Inc., 2016)
"What do you do with a chance? Especially one that seems too big or too wild or just out of reach? Do you hold back? Do you act like you don't care? Do you let it slip away? This is the story of some remarkable chances and the child who doesn't know quite what to do with them. But the more chances come around, the more the child's fascination grows. And then, one day, a little courage makes all the difference in the world"--Dust jacket.
Booklist
Kirkus Review
School Library Journal
Booklist, December 2017
Kirkus Review, November 2017
School Library Journal, January 2018
Keywords: Children Stories. -- Juvenile fiction; Picture Books. -- Juvenile fiction; Picture books